Value Preferences Predicting Narcissistic Personality Traits in Young Adults - (:unkn) unknown (EDAM, 2012)
This study aimed at showing how the value preferences of young adults could predict the narcissistic characteristics of young adults according to structural equation modeling. 133 female (59.6%) and 90 male (40.4%), total 223 young adults participated the study (average age: 25.66, ranging from 20 to 38). Ratio group sampling method was used while choosing the participants. In order to collect data 'Narcissistic Personality Inventory and Schwartz's Value Scale were used. The theoretical model was tested in terms of structural equation modeling by using AMOS 16 program. The study revealed that power, success, hedonism, excitation, self-control and universality have positive effects on narcissism, while benevolence, safety have a negative effect on narcissism. Although being quite weak and powerless, narcissistic personalities are always in need of power towards outer world. This enforces them to exist despite the other. On the other hand the need of benevolence and safety enforce people to take notice of others and exist together with the other.
Keywords: Personality; Narcissistic Personality; Value; Schwartz's Value Scale; FIT